Pt modified TiO2/NiO p-n junction with enhanced surface reaction and charge separation for efficient photocatalytic hydrogen evolution. (5th March 2022) - Liang, Zikun; Ouyang, Bo; Wang, Tongyu; Liu, Xuan; Huo, Hailing; Liu, Dong; Feng, Hao; Ma, Jingjing; Deng, Kaiming; Li, Ang; Kan, Erjun
Abstract: Efficient charge separation is crucial for solar energy conversion in semiconductor-based systems. Creating p-n junction is an effective strategy to enhance charge separation because the built-in electric field could inhibit charge recombination. However, in many situations, the high reaction barrier will limit the surface reaction rate, resulting in poor carrier utilization of the p-n junction. Here, with carefully designed cocatalyst loading, we successfully overcome the limitation and obtain the full effectiveness of the p-n junction. When used for photocatalytic water splitting, the well-designed catalyst exhibits excellent photocatalytic activity, with a hydrogen evolution rate as high as 13.2 mmol h −1  g −1, which is 18 times higher than that of the pristine p-n junction. Further investigation reveals that the enhancement should be attributed to the synergistic effect between cocatalyst and p-n junction, with the cocatalyst improves reaction rate on the surface and the p-n junction accelerates charge separation in the bulk simultaneously. This work provides an effective strategy to modify the surface properties of p-n junction through cocatalysts-loading for efficient photocatalytic hydrogen evolution. Graphical abstract: Image 1 Highlights: Cocatalyst is effective to improve the sluggish surface reaction of p-n junction. TiO2 /NiO–Pt showed high stability and excellent photocatalytic hydrogen evolution activity of 13.2 mmol g −1  h −1 . Efficient charge separation and carrier utilization can be realized in the system of cocatalyst loaded p-n junction. Cocatalyst and p-n junction contribute a synergistic effect towards photocatalytic water splitting.